Pendampingan Optimalisasi Promosi Objek Wisata River Tubing Kokok Babak di Desa Persiapan Benue Kecamatan Batukliang Kabupaten Lombok Tengah - Islahudin, Islahudin; Utami, Linda Sekar; Hamzah, Hamzah; Sabaryati, Johri; Ramdhan, M. Firman; Rupiarti, Riski Mini; Putri, Suci Pebriyanti; Aryansyah, Aryansyah (Abdimas Mandalika, 2025)
Abstract:  This community service activity involved a partner, namely the Preparatory Village of Benue. The objectives of this program were: 1) to conduct a socialization session about the Community Service Program (KKN) carried out by Universitas Muhammadiyah Mataram, with the aim of placing students in the Preparatory Village of Benue in the future; and 2) to assist in creating unique and attractive promotional videos and infographics related to the River Tubing tourist attraction at Kokok Babak, which could be distributed primarily through social media. The method used in this community service consisted of three stages: 1) preparation stage, 2) implementation stage, 3) implementation stage (note: this is repeated in the source), and 3) monitoring and evaluation. Based on the results of the socialization and implementation, it can be concluded that: 1) 90% of the staff in the Preparatory Village of Benue have understood the KKN program organized by Universitas Muhammadiyah Mataram, which opens the opportunity for future student placements; and 2) 90% of the river tubing tourist site has been recorded, and the promotional videos have been created in an engaging and creative manner and successfully disseminated through Facebook and YouTube.Abstrak: Kegiatan pengabdian ini memiliki mitra yaitu Desa Persiapan Benue. Tujuan pengabdian ini yaitu 1) memberikan sosialisasi terkait program KKN yang dilaksanakan oleh Universitas Muhammadiyah Mataram agar ke depan bisa menempatkan mahasiswa di Desa Persiapan Benu; 2) membantu membuatkan video promosi dan infografis yang unik dan menarik terkait objek wisata River Tuning Kokok Babak sehingga bisa disebar terutama melalui media sosial. Metode yang digunakan pada kegiatan pengabdian ini terdiri dari 3 langkah yaitu 1) tahap persiapan, 2) tahap pelaksanaan, 3) tahap implementasi, dan 3) monitoring dan evaluasi. Berdasarkan hasil sosialisasi dan implementasi pengabdian kepada masyarakat tersebut dapat disimpulkan yaitu 1) sebesar 90% staf di Desa Persiapan Benue sudah memahami terkait program KKN yang dilaksanakan oleh Universitas Muhammadiyah Mataram agar ke depan bisa menempatkan mahasiswa di Desa Persiapan Benue; 2) sebesar 90% lokasi wisata river tubing sudah direkam dan dibuatkan video promosinya secara menarik dan unik serta sudah disebar melalui facebook dan youtube.